Variation in bioactive content in broccoli (Brassica oleracea var. italica) grown under conventional and organic production systems. (30th July 2014) - Valverde, Juan; Reilly, Kim; Villacreces, Salvador; Gaffney, Michael; Grant, James; Brunton, Nigel
Abstract BACKGROUND Broccoli and other cruciferous vegetables contain a number of bioactive compounds, in particular glucosinolates and polyphenols, which are proposed to confer health benefits to the consumer. Demand for organic crops is at least partly based on a perception that organic crops may contain higher levels of bioactive compounds; however, insufficient research has been carried out to either support or refute such claims. RESULTS In this study we examined the effect of conventional, organic, and mixed cultivation practices on the content of total phenolics, total flavonoids, and total and individual glucosinolates in two varieties of broccoli grown over 2 years in a split‐plot factorial systems comparison trial. Levels of total phenolics and total flavonoids showed a significant year‐on‐year variation but were not significantly different between organic and conventional production systems. In contrast, levels of the indolyl glucosinolates glucobrassicin and neoglucobrassicin were significantly higher (P < 0.05) under fully organic compared to fully conventional management. CONCLUSION Organic cultivation practices resulted in significantly higher levels of glucobrassicin and neoglucobrassicin in broccoli florets; however, other investigated compounds were unaffected by production practices. © 2014 Society of Chemical Industry